THU0514 Predictive value of subclinical synovitis detected by doppler ultrasound in relation to flare in patients with juvenile idiopathic arthritis treated with biologic therapy after tapering biologic therapy. (15th June 2017) - Nieto-González, JC; Boteanu, A; Lόpez-Robledillo, JC; Collado, P; Rodríguez, A; Clemente, D; Gámir, ML; Monteagudo, I; Naredo, E
Abstract : Background: Anti-TNF therapy is effective and safe in JIA. Changes in anti-TNF doses are common when remission is achieved 1 . Subclinical synovitis on Doppler mode (PD) detected by ultrasound can predict flares in adult RA, but it is not yet clear in JIA 2 Objectives: The aim of this study is to evaluate the predictive value of subclinical synovitis detected by PD-US in relation to flares in patients with JIA on remission under anti-TNF when therapy is tapered. The preliminary results were presented at the EULAR congress 2015 in Rome (FRI0520). Methods: Observational, prospective and multicenter study. We included JIA patients on remission at least 6 months with anti-TNF, ETN and ADA, in whom anti-TNF was tapered due to clinical decision. ETN was tapered by increasing the injection 3 days and ADA by increasing a week. Patients were clinically assessed every 3 months and also with PD-US at baseline. Bilateral US assessment included joints and tendons. Adult synovitis definitions and semiquantitative scoring system were used, no synovitis definitions are available for JIA. We collected demographics (date of birth, JIA subcategory, previous and current treatments. Flare was defined as clinical signs and/or symptoms of arthritis that required increase of systemic therapy Results: We included 57 patients, with 19 patients (33.33%) having a flare during the 12 months follow-up. 38 patients (66.67%) were receiving ETN and 19 (33.3%) ADA, of which 11 patients (28.95%) had a flare with ETN and 8 patients (42.11%) with ADA. Table 1 shows demographics. Median time to flare was 5.73 months (IR 2–93–8.9). Concomitant methotrexate was lower in patients with flare (26.32% vs 71.05%). In 18 patients (31.58%), a previous tapering was done and median time of remission before being included was 22 months (IR 15.5–28.5). US does not predict flare in our cohort. Global synovitis score at baseline was 4 (IQR 1.3–10.8) and 0 in BM and PD respectively, and tenosynovitis was 0 both BM and PD Conclusions: Anti-TNF tapering was safe in our JIA patients in more than half of patients after 1 year follow-up. US did not predict flares in our patients. Concomitant treatment with methotrexate was more frequent in patients who remained on remission References: Cai Y. Rheumatol Int.2013. Magni-Manzoni S.Ann Rheum Dis.2013. Disclosure of Interest: None declared